2011
DOI: 10.1016/j.ajpath.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Increases Hyaluronan in Surrounding Nonmalignant Stroma, and This Response Is Associated with Tumor Growth and an Unfavorable Outcome

Abstract: Our objective was to investigate whether the presence of a tumor increases hyaluronan (HA) levels in surrounding prostate tissues and whether this extratumoral HA influences tumor growth and outcome. From a series of 287 men diagnosed with prostate cancer at transurethral resection and followed up with watchful waiting, tissue microarrays were constructed, stained, and scored for HA. A high HA staining score in the tumor stroma or in nonmalignant prostate tissue stroma were both associated positively with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 49 publications
(63 reference statements)
5
68
0
Order By: Relevance
“…Moreover, elevated HA levels in pleural effusion was associated with increased survival in MPM, in line with a previous study [72,75]. In contrast, five studies on prostate, gastric, colon and breast cancers suggested that increased stromal HA was associated with poor prognosis [76][77][78][79]. One possible explanation for this could be that the production of HA could be higher in well differentiated, less aggressive MPM tumor cells [75].…”
Section: Hyaluronatesupporting
confidence: 63%
“…Moreover, elevated HA levels in pleural effusion was associated with increased survival in MPM, in line with a previous study [72,75]. In contrast, five studies on prostate, gastric, colon and breast cancers suggested that increased stromal HA was associated with poor prognosis [76][77][78][79]. One possible explanation for this could be that the production of HA could be higher in well differentiated, less aggressive MPM tumor cells [75].…”
Section: Hyaluronatesupporting
confidence: 63%
“…Irrespective of the obvious differences between a short-term rat tumor-implantation model and patients, our studies in prostate cancer patients suggest that some of the changes in TINT seen in the rat model are also present in and related to tumor aggressiveness in patients—for example, increased vascular density, accumulation of inflammatory cells, and alterations in the extracellular matrix [1, 8, 9, 13, 22]. Altered gene expression in histologically normal tumor-adjacent tissue relative to that in normal prostate tissue from men without prostate cancer has also been found in other studies [17, 2326].…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with animal experiments showing that vascular density is increased in the surrounding normal tissue after orthotopically implanted tumours [43]. Previously, in the same material, the authors have found that high expression of phosphorylated EGF-R in the glandular epithelium and high platelet-derived growth factor receptorb (PDGFR-b), high hyaluronan levels, high numbers of mast cells and low numbers of androgenpositive cells in the stroma of the normal tissue (TINT) surrounding cancer are related to poor outcome [32,33,[44][45][46].…”
Section: Discussionmentioning
confidence: 95%